Anemia Reduction Program In Adolescents: Scoping Review - Fatimah, Siti; Rosyad, Shelly Rodliah; Wulandatika, Darmayanti (P3M Universitas 'Aisyiyah Surakarta, 2024)
Introduction : Anemia is a health problem that causes sufferers to experience fatigue, fatigue and lethargy. Anaemia is estimated to affect half a billion women 15–49 years of age in worldwide and in indonesia the prevalence of anemia in adolescents is 32%, This article aims to identify programs related to the treatment of anemia in adolescents, support and obstacles in the implementation of anemia reduction programs. Method: This article used Arshey & O’Malley Framework; selecting articles of which search flow is described through PRISMA Flowchart. Results: Based on 10 chosen articles, 6 articles are marked very good quality and 4 articles are marked as a good quality. Furthermore, there are 2 obtained main themes; Program Form and Barriers. Conclusion: The use of educational media and socialization related to anemia and its prevention for adolescents is expected to increase knowledge and awareness of adolescents about the importance of preventing anemia for adolescents.